Relationship between the hadley circulation and tropical SST meridional structures under different thermal conditions in the indo-pacific warm pool - Ji, Xuanliang; Feng, Juan; Li, Jianping; Chen, Xingrong (Frontiers in Marine Science, 2023)
Based on the multiple atmospheric reanalyses and sea surface temperature (SST) datasets, the modulation of Indo-Pacific warm pool (IPWP) thermal conditions on the relationship between the Hadley circulation (HC) and tropical zonal-mean SST under different meridional structures was investigated. By decomposing the variations of HC and SST into two components, one equatorially asymmetric component (HEA for HC, SEA for SST) and one equatorially symmetric component (HES for HC, SES for SST), the connections of HC to different SST variations in the warm and cold IPWP are explored. The result demonstrates that the relationship of the HC to tropical SST is suppressed in the cold IPWP conditions, whereas it is equivalent to the climatology in the warm IPWP conditions. The plausible mechanism is that the cold (warm) IPWP events are in concordance with the La Niña (El Niño) decay events. The La Niña decay events are associated with significant equatorially asymmetric SST anomalies within the IPWP, generating an anomalous meridional circulation and favoring a strengthened equatorially asymmetric anomalous meridional circulation. By contrast, the SST anomalies associated with El Niño decay events are insignificant. The role of La Niña decay conditions in determining the suppressed connection between SST and HC is further verified by exploring the result after 1979. A similar suppressed response contrast between the HC and tropical SST has been detected. Therefore, the results demonstrate that warm and cold ENSO events have impacts on the interannual thermal conditions of IPWP, whereby interannual variation of IPWP thermal conditions plays considerable role in impacting the relationship between the HC and tropical SST. Particularly, with the rapid warming, the interconnection between ENSO events and thermal conditions of IPWP under different time-scales could be altered, the influence of which on the responses of the HC to tropical SST remains uncertain and is worthy further researching.